2015
DOI: 10.1007/s10965-015-0736-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel single-component composite based on phthalonitrile end-capped polyarylene ether nitrile: crystallization and crosslinking

Abstract: A novel single-component composite based on phthalonitrile end-capped polyarylene ether nitrile (PEN-Ph) was prepared successfully via hot compression. In the PENPh system, the crosslinking reactions and crystallization exist simultaneously, and the crystals are embedded in the crosslinked PEN-Ph matrix, which can work as reinforcement. Analysis of the Non-isothermal cold crystallization kinetics of the PEN-Ph system was performed by using differential scanning calorimetry (DSC), and the activation energy of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…It is obviously observed that there is a steamed‐bun‐like peak in the range of 10–30° both in the samples of blending PEN‐Ph film and pure HMW PEN‐Ph film, which is attributed to the amorphous background resin. For the blending PEN‐Ph film [Figure (a)], there are three diffraction peaks at 17.0, 18.2, and 23.3°, indicating that the film with LMW PEN‐Ph loading does have crystallization properties . These XRD analysis results are consistent with the DSC analysis results.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…It is obviously observed that there is a steamed‐bun‐like peak in the range of 10–30° both in the samples of blending PEN‐Ph film and pure HMW PEN‐Ph film, which is attributed to the amorphous background resin. For the blending PEN‐Ph film [Figure (a)], there are three diffraction peaks at 17.0, 18.2, and 23.3°, indicating that the film with LMW PEN‐Ph loading does have crystallization properties . These XRD analysis results are consistent with the DSC analysis results.…”
Section: Resultssupporting
confidence: 78%
“…Thus, as the LMW PEN‐Ph content increases, the crystalline degree of PEN‐Ph film which is reflected by the melting enthalpy increases, and the values of the melting enthalpy are listed in Table . During the process of crystal melting, the lamellae will be thickening, perfecting, and recrystallizing, so that the sample possess a broad melting peak as well as long melting range . On the one hand, at the temperature of 280 °C, the crosslinking reaction hardly occurs; thereby, the LMW PEN‐Ph is acting as plasticizer.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the certain regular structure of the molecular chain and the phthalonitrile groups at the end of the molecular chain, PEN-Ph possesses crystallization properties combined with crosslinking properties [14,15]. In this work, the crystallization behavior and crosslinking behavior were studied.…”
Section: Introductionmentioning
confidence: 99%
“…The most important property of it is the self‐crosslinking. Based on these properties, Tong and her co‐workers have fabricated the single component cross‐linked composite films , whose T g was improved by a large margin. However, the improvement of T g and thermal resistance were at a sacrifice of flexibility, dielectric constant as well as tensile strength .…”
Section: Introductionmentioning
confidence: 99%